A STUDY OF SIGNIFICANT OF MINDFULNESS AND MENTAL ILLNESS BASED ON ISLAMIC PSYCHOTHERAPY (Journal of Pharmaceutical Negative Results, 2022)
Mindfulness in Islam is akin to muqarabah, which refers to an individual’s practices in a situation where he has completely surrendered himself to Allah SWT. A person who has forgotten Allah S.W.T and doing Allah S.W.T 's prohibition will suffer two types of punishments for his actions as mentioned on above verses. Allah S.W.T will disregard his servant. He will not help his servant to gain a happiness in this world and will just let his servant suffer in their difficulty. Allah S.W.T will make they forget about their true self. The darkened heart will make them not aware of the sins committed, and they will ignore their surroundings. If a person feels this is a problem to them, it’s obvious that they have forgotten the good that Allah S.W.T. It will become more relevant when they are approached by death and the Judgement Day because what’s been done in the world will be accumulated during the hereafter. There are three stages of ignorance. Forget and ignore Allah S.W.T, His Names, His attributes, and His essences (Taqwa). Do not carry out Allah S.W.T orders, such as does not perform daily prayers, paying zakat, helping people in need, serving the orphans and more.